If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + -4) = 2 Reorder the terms: x(-4 + x) = 2 (-4 * x + x * x) = 2 (-4x + x2) = 2 Solving -4x + x2 = 2 Solving for variable 'x'. Reorder the terms: -2 + -4x + x2 = 2 + -2 Combine like terms: 2 + -2 = 0 -2 + -4x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '2' to each side of the equation. -2 + -4x + 2 + x2 = 0 + 2 Reorder the terms: -2 + 2 + -4x + x2 = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -4x + x2 = 0 + 2 -4x + x2 = 0 + 2 Combine like terms: 0 + 2 = 2 -4x + x2 = 2 The x term is -4x. Take half its coefficient (-2). Square it (4) and add it to both sides. Add '4' to each side of the equation. -4x + 4 + x2 = 2 + 4 Reorder the terms: 4 + -4x + x2 = 2 + 4 Combine like terms: 2 + 4 = 6 4 + -4x + x2 = 6 Factor a perfect square on the left side: (x + -2)(x + -2) = 6 Calculate the square root of the right side: 2.449489743 Break this problem into two subproblems by setting (x + -2) equal to 2.449489743 and -2.449489743.Subproblem 1
x + -2 = 2.449489743 Simplifying x + -2 = 2.449489743 Reorder the terms: -2 + x = 2.449489743 Solving -2 + x = 2.449489743 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + x = 2.449489743 + 2 Combine like terms: -2 + 2 = 0 0 + x = 2.449489743 + 2 x = 2.449489743 + 2 Combine like terms: 2.449489743 + 2 = 4.449489743 x = 4.449489743 Simplifying x = 4.449489743Subproblem 2
x + -2 = -2.449489743 Simplifying x + -2 = -2.449489743 Reorder the terms: -2 + x = -2.449489743 Solving -2 + x = -2.449489743 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + x = -2.449489743 + 2 Combine like terms: -2 + 2 = 0 0 + x = -2.449489743 + 2 x = -2.449489743 + 2 Combine like terms: -2.449489743 + 2 = -0.449489743 x = -0.449489743 Simplifying x = -0.449489743Solution
The solution to the problem is based on the solutions from the subproblems. x = {4.449489743, -0.449489743}
| -10z-2=-z+7 | | r^2+24r+169=0 | | 2p^2=-18p | | 4d^2+15d-4= | | 5+8(x-2)=(3x+1)4+1 | | Y=5/2x-5 | | 4/(1-x)=5/(1+x) | | c^2-9c= | | 13/(2x-3)=11(x+3) | | 13/2x-3=11x+3 | | -15t^2+60t+10=0 | | 4x-2.1=-6.3+1.9x | | 3x^2+4x-17=0 | | (x+1/x)^2-5(x+1/x)+6=0 | | 5/6x+1+3 | | 3j-7j=12 | | (x-9)(5x+12)=0 | | 121=r^2 | | 625=r^2 | | 324=r^2 | | 2x+5=3+5x | | 6-5=4x+1 | | 6x+5=4x+1 | | 5805.86=3.14r^2 | | 4j-9j+3=-3 | | (x-7)(y-5)= | | (5x)=(3x+28) | | (3x-1)(3-8x)= | | y=4(7x+100) | | y=1/2+5(0,3) | | (8k-9)(3k-7)= | | 36^1/2 |